Perception and acoustic features of Lithuanian directive phrases: a preliminary study - Kazlauskienė, Asta (Baltistica, 2025)
The aim of this study is to identify the acoustic similarities and differences of selected Lithuanian directive phrases and to assess their potential impact on phrase type perception. The research material consists of sentences read seven times by three male actors, simulating assertion, request, supplication, permission, and command. For the perception experiment, one typical phrase of each type was selected from each speaker, with three additional samples from different speakers. Twenty-two participants were asked to identify the phrase types. The results show that command was identified most accurately (94%), while permission (73%) and assertion (67%) were less reliably identified; request and supplication were poorly identified (54% each). Participants relied partly on lexical-semantic and grammatical cues. For this reason, command and permission (Dabar eikite namo [dɐ²ˈbɐrˑ ²ˈɛɪˑkʲɪtʲɛ nɐ²ˈmoː‖] – “Go home now”) were not confused with supplication and request (Dabar norime eiti namo [dɐ²ˈbɐrˑ ¹ˈnoːrʲɪmʲɛ ²ˈɛɪˑtʲɪ nɐ²ˈmoː‖] “We want to go home now”) or assertion (Dabar galime eiti namo [dɐ²ˈbɐrˑ 2ˈɡɑːlʲɪmʲɛ 2ˈɛɪˑtʲɪ nɐ2ˈmoː‖] – “We can go home now”), though the latter were often confused with each other. The analysis of acoustic parameters considered: (a) mean, maximum, range, register, and contour of F0; (b) mean, maximum, range, and curve of intensity; (c) duration of words, syllable nuclei, and consonants. The findings indicate: (1) F0 parameters were generally similar, except for permission, which was produced with higher pitch; all phrases shared comparable intonation models: flat low (without narrow focus) or falling and rising–falling (with narrow focus); (2) permission exhibited the lowest intensity, while supplication, request, and assertion were produced with higher intensity, and command demonstrated the widest intensity range; all phrases ended with slightly lower intensity than at the beginning; (3) in terms of duration, supplication stood out with the longest segments across all categories, while command was characterized by consonant shortening.